Test-retest reliability of handgrip muscle function among Australian rules football athletes - Mathews, L. O.; Jaekel, H. R.; Ridgers, N. D.; Catley, M. J.; Tomkinson, G. R. (Journal of Exercise Science & Fitness, 2026)
Background/objective Advancements in handgrip dynamometry provide unique opportunities to measure multiple aspects of handgrip muscle function. The aim of this study was to quantify the test-retest reliability of handgrip muscle function among athletes using digital handgrip dynamometry.